APOLIPOPROTEIN B/A1 IS INDEPENDENTLY ASSOCIATED WITH CAROTID INTIMAL-MEDIAL THICKNESS IN CHRONIC KIDNEY DISEASE PATIENTS. - Il Young Ki; m; Soo Bong Lee; Dong Won Lee; In Hye Hwang; Kyung Nam Lee; Min Ji Shin; Harin Rhee; Sang Heon Song; Eun Young Seong; Ihm Soo Kwak (The Korean Society of Nephrology, 2012)
Serum apolipoprotein B/A1 (apo B/A1) ratio has been known for strong predictor of cardiovascular disease (CVD). Measuring carotid artery intimal-medial thickness (CIMT) is non-invasive modality used to evaluate subclinical atherosclerosis and to predict future cardiovascular disease. The objective of this study is to evaluate the association between apo B/A1 and CIMT in chronic kidney disease (CKD).We retrospectively reviewed the 293 patients who had visited health promotion center in a single community. The patients were divided into 2 group which are CKD group (n=99, estimated glomerular filtration rate (eGFR): 15-59 mL/min) and non-CKD group (n=194, eGFR ≥ 60 mL/min). Age, sex, presence of diabetes mellitus (DM)/hypertension, smoking status, eGFR, body mass index, and various biochemical blood examinations (serum LDL/HDL cholesterol, serum homocystein, and serum apo B/A1 ratio) were evaluated in each patient. CIMT was measured by high-resolution B-mode ultrasonography. Multivariate linear regression analysis was performed to investigate which factors are associated with CIMT in each of 2 groups. In CKD group, age (β=0.163, p=0.024), presence of hypertension (β=0.208, p=0.006), and presence of DM (β=0.236, p=0.002) were independently associated with CIMT adjustment for other confounding factors. However, in CKD group, serum apo B/A1 (β=0.572, p<0.001), presence of HTN (β=0.360, p=0.001), and presence of DM (β=0.194 p=0.023) contributed to CIMT independently after adjustment for other confounding factors. In conclusion, this study showed serum apo B/A1 ratio was independently associated with CIMT only in CKD group, not in non-CKD group. Because CIMT is a strong predictor of CVD, the result of this study demonstrates serum apo B/A1 ratio could be included in cardiovascular risk stratification in CKD patients